Well-controlled gestational diabetes mellitus without pharmacologic therapy decelerates weight gain in infancy - Li, Chao; Cai, Yixi; Li, Yinying; Peng, Bin; Liu, Yongfang; Wang, Zhenming; Yang, Ting; Hu, Yirong; Fu, Yajun; Shi, Tingmei; Peng, Hong; Zhang, Yue; et al. (Frontiers in Endocrinology, 2022)
Aim There are no prospective longitudinal studies on the association between well-controlled gestational diabetes mellitus (GDM) without pharmacologic therapy and the physical growth of offspring in infancy. We aimed to identify the trajectories in physical growth (from 0–12 months of age) in the offspring of mothers with well-controlled GDM without pharmacologic therapy in a prospective cohort in China. Methods This study included 236 offspring of mothers with GDM and 369 offspring of mothers without GDM. Mothers with GDM were not on pharmacologic therapy. The length and weight of infants were measured at 0, 1, 3, 6, and 12 months. Linear mixed-effect models and linear mixed-effect models were applied. Results The fully adjusted model showed that the weight-for-age z-score (WAZ), length-for-age z-score (LAZ), and BMI-for-age z-score (BMIZ) were similar at birth for the GDM and control groups. However, subsequent increases in WAZ and BMIZ for the GDM group lagged the increases for the control group at the subsequent periods of observation, 0–1, 0–6, and 0–12 months. Conclusions Well-controlled GDM without pharmacologic therapy may normalize physical growth of offspring at birth and decelerate their weight gain in infancy. Whether glycemic control can mitigate the long-term effects of GDM on the growth trajectory in offspring remains unclear.